Webinar Series: Listening to Learn— Sessions during 2022–2023 - Gupta, Gagan (SCHOOL SCIENCE, 2023)
The NCERT’s Telecast Programme Webinar Series: ‘Listening to Learn’ continued during the financial year 2022–23. During the year; twenty-one sessions were organised on a wide range of topics related to school education. It included astronomy—gravitational lensing and James Webb Telescope; environment—soil-water quality, rivers, hydroelectric cells and water; biological sciences and medicine—genetic engineering, biosecurity, radiology, superbugs and brain; archeology and earth sciences— dinosaurs, geophysics and radionuclides; engineering sciences and applications— nuclear radiations, materials, wind tunnels, cells and batteries, and biomimicry. A session for motivating children for entrepreneurship was also organised by the Mumbai Dabbawallas.